2008
DOI: 10.1016/j.addr.2007.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic materials for tissue engineering

Abstract: Tissue engineering and regenerative medicine is an exciting research area that aims at regenerative alternatives to harvested tissues for transplantation. Biomaterials play a pivotal role as scaffolds to provide three-dimensional templates and synthetic extracellular-matrix environments for tissue regeneration. It is often beneficial for the scaffolds to mimic certain advantageous characteristics of the natural extracellular matrix, or developmental or would healing programs. This article reviews current biomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
819
0
18

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,212 publications
(874 citation statements)
references
References 132 publications
6
819
0
18
Order By: Relevance
“…The fabrication technologies used for scaffold fabrication in cartilage tissue engineering included electrospinning (Wise et al, 2009), particulate leaching combined with chemical etching Park et al, 2005) and 3-D printing techniques (Yen et al, 2009). L-L TIPS is an easy and effective technique to fabricate 3D nano-fibrous scaffolds (Ma, 2008;Zhang and Ma, 1999). A homogeneous polymer-solvent system would spontaneously undergo a liquid-liquid phase separation when thermodynamically quenched into the unstable zone under the spinodal curve, resulting in a separated polymerrich phase and a polymer-poor phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fabrication technologies used for scaffold fabrication in cartilage tissue engineering included electrospinning (Wise et al, 2009), particulate leaching combined with chemical etching Park et al, 2005) and 3-D printing techniques (Yen et al, 2009). L-L TIPS is an easy and effective technique to fabricate 3D nano-fibrous scaffolds (Ma, 2008;Zhang and Ma, 1999). A homogeneous polymer-solvent system would spontaneously undergo a liquid-liquid phase separation when thermodynamically quenched into the unstable zone under the spinodal curve, resulting in a separated polymerrich phase and a polymer-poor phase.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, intensive studies showed that cells recognized nanometric topologies of fibrous or microporous structure (Laurencin et al, 1999). Such a nanoscale structure, which geometrically mimicked the native state of the extracellular matrix (ECM), could selectively enhance protein adsorption and consequentially enhance cell attachment (Woo et al, 2003), and it therefore received much academic attention in medical applications (Ma, 2008). Zhang and Ma pioneered the preparation of PLLA nano-fibrous scaffolds with a fiber diameter ranging from 50 to 500 nm through thermally induced liquid-liquid phase separation (L-L TIPS) (Ma and Zhang, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the release kinetics of the target biomolecules can be modulated by changing the composition of the particulate carrier system, the amount of drug encapsulated and the size of the micro/nanoparticles. However, when micro/nanoparticles are incorporated into prefabricated porous scaffolds, they often tend to aggregate, which may not serve the purpose of controlled/spatial delivery of biomolecules (Langer, 1998;Jeong et al, 1997;Ma, 2008). One approach to overcome these limitations is to suspend the biomolecules-loaded micro/nanoparticles into biomaterial solutions during the crosslinking phase of scaffold fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…The extracellular matrix (ECM) is a model used for inspiration when designing biomimetic scaffolds for tissue engineering [3]. By mimicking the structure and/or surface properties of the naturally occurring ECM, engineers may be able to influence cell growth and tissue formation.…”
Section: The Scaffold As a Temporary Extracellular Matrixmentioning
confidence: 99%